Perfo 4. (Rotterdam : Lantaren / Venster, 1986)
Van Lieshout, Joep ; Noordermeer, Jaap ; Esguerra, Diane ; Smith, Michael ; Mass and Individual Moving ; Techler, Andreas ; Stitt, André ; Uil, Bram ; Vertessen, Liliane ; Rose, Jon ; Wiegman, Diet ; Smits, George ; Finly, Karen ; McRae, Peter ; Friedman, Ken ; Lizène, Jacques ; Zep ; Van Keulen, Floor ; Farioli, Daniel ; Janssen, Servie ; Horvers, Toine ; etc.
Perfo 4, Lantaren / Venster, Rotterdam, 19 t.m 27 september 1986
boek